A Multicomponent Home-Based Intervention for Neuropsychiatric Symptoms in People With Dementia and Caregivers' Burden and Depression: A 6-Month Longitudinal Study. (July 2022) - Mougias, Antonis A.; Christidi, Foteini; Kontaxopoulou, Dionysia; Zervou, Mariyanna; Kostoglou, Dimitra; Vlami, Maria Anna; Dimitriou, Maria; Politis, Antonis
Objectives: Many people with dementia live in their home and require ongoing care, which is often provided by informal family caregivers. Thus, we examined the effectiveness of a multicomponent home-based intervention by evaluating its impact on a) neuropsychiatric symptoms of people with dementia and b) burden and depression of their caregivers. Methods: During the first 6 months of this prospective single-center study, we applied a home-based multicomponent intervention in 205 dyads of care-recipients and caregivers. In further analyzes, we included only dyads of caregivers and care-recipients with available data both at baseline and 6-month follow-up (N = 144). All assessments were conducted at home and included sociodemographic features, care-recipients' clinical data, cognitive status (Mini-Mental State Examination), activities of daily living (Instrumental Activities of Daily Living; Katz Index of Independence in Activities of Daily Living), neuropsychiatric symptoms (Neuropsychiatric Inventory), and caregivers' burden (Zarit Burden Inventory) and depression (Center for Epidemiological Studies-Depression). Results: We found significant decreases in the severity (pFDR = 0.002) and associated distress (pFDR = 0.001) of neuropsychiatric symptoms, as well as caregivers' burden (pFDR = 0.004) and depressive symptoms (pFDR = 0.001). As expected, there was significant deterioration in care-recipients' cognitive status (pFDR = 0.005) and measures of activities of daily living (pFDR < 0.005). Conclusion: Despite the progressive course of dementia, the home-based multicomponent intervention was effective in decreasing caregivers' burden and depression and minimizing care-recipients' neuropsychiatric symptoms' severity and associated distress after 6 months. Our study highlights the establishment of home-based care units as an advantageous solution, specifically for family members seen to have a "taken-for-granted" role in dementia caring.